Parents’ Experiences of Change in Developmental and Transactional Processes After Time-Limited Intersubjective Child Psychotherapy – A Qualitative Study - Fiskum, Charlotte; Johns, Unni Tanum; Andersen, Tonje Grønning; Jacobsen, Karl (Frontiers in Psychology, 2022)
Psychopathology in children cannot be understood without considering developmental processes and transactional relationships, particularly the relationship with caregivers. Time-limited intersubjective child psychotherapy (TIC) is a developmental and transactional approach aimed at helping children and caregivers get back on healthier developmental trajectories. Core developmental processes, such as self-other-regulation and affect integration, are considered particularly important for healthy function and transactions with caregivers and contexts. Therefore, TIC seeks to strengthen core developmental processes in the child and the caregivers’ ability to scaffold the child’s development. This is achieved through parallel child therapy and parent sessions. The current study is a qualitative study of parents’ experiences of change after TIC. The study explores parents’ perception of change in their child, themselves, and their transactions, and what they experienced as helpful in therapy. Materials and Methods Nine semi-structured qualitative interviews were conducted with parents (n = 13) of nine children aged 9–12 years with internalizing difficulties after completing TIC. The data were analyzed with thematic analysis. Results The parents described positive changes in the children’s ability to understand, regulate and express themselves. The parents also described positive changes in their parenting, and for all nine children the parents reported positive changes in the transactions between themselves and the child. Most parents saw the parallel child and parental sessions as particularly important, while several parents mentioned play and the therapeutic focus. Discussion Parents’ description of changes after TIC indicate that the parents perceived their children as strengthened in core developmental processes important for intersubjective exchanges such as self-regulation and affect integration. In addition, parents saw their children and their own contributions more clearly, and their transactions were described as more supportive and positive. Conclusion The results from this study give support to TIC as a developmentally supportive approach to therapy, with potential effects on children’s core developmental processes, their parents’ ability to both see and scaffold the child’s development and positive effects on the transactions between children and parents. The positive effects likely result from the integration of the different parts of TIC and the synergies taking place between them, rather than any one component by itself.